Sources of solar tracking errors and correction strategies for heliostats - Maiga, Mahamadou; N’Tsoukpoe, Kokouvi Edem; Gomna, Aboubakar; Fiagbe, YesuenyeagbeA.K. (Renewable & sustainable energy reviews, 2024)
Heliostat fields represent the primary energy input for concentrating solar-thermal power based on power tower technology. They typically account for 40 %–50 % of the implementation cost of a power tower plant. Therefore, it is essential to optimize the solar tracking accuracy of heliostats to reduce solar tracking errors that lead to deviations in the reflected rays from the receiver. Solar tracking errors are a significant contributor to thermal energy loss in power tower plants, and their sources have been the subject of numerous studies. An overview of these studies on error sources currently constitutes a gap. This review presents the contributions of these studies to the understanding of focal spot deviation caused by error sources in the operation of heliostats and the possible correction methods for such deviations. Furthermore, the review discusses the potential causes of the various errors and the accuracy of correcting a given error source with a given approach or strategy based on available data. The objective is to provide a state-of-the-art overview of the correction and analysis of solar tracking error sources in heliostats. This contribution will help improve the design of heliostat solar tracking, which is one of the most significant challenges for power tower plants. [Display omitted] •The solar tracking error sources of heliostats in power tower plants are reviewed.•The state of the art for analyzing and correcting error sources is presented.•Gravity and wind loads, creep, rainfall, and soil properties cause the most errors.•Spot deviation depends on the error magnitude, heliostat position, and season.•Mathematical model-based solar tracking corrects most errors.